Digital keywords for China: perceptions and portrayals in English-language novels - Matthews, Graham (2023)
As China emerges as a potential global superpower, it is more important than ever to recognise and analyse the ways in which the country has been represented in literature and culture. English-language novels frequently include passing reference to China but these instances are usually too minor to contribute to the major themes of the novel and pass without comment in traditional forms of literary scholarship. When collected together, these references are indicative of the ways in which the cultural perception of China has fluctuated and changed over the decades. We examined 8,438 English-language novels across a period of over one hundred years in order to trace broad patterns and shifts in the literary representation of China over the course of the twentieth and early twenty-first centuries. To date, we have collected 12,186 passages that include the words china or chinese with full metadata (author, title, country of origin, year of publication) for the years 1900–2017. We have generated a coding scheme to identify keywords; these include tea, communism, emperor, crime, and foot-binding. Analysis of particular keywords with reference to the corresponding sets of quotations reveals fresh insight into the literary and cultural construction of China that has shaped public perception. The accompanying database is released under the Creative Commons Attribution 4.0 International (CC BY 4.0) license.